High Shear Homogenization of Lignin to Nanolignin and Thermal Stability of Nanolignin‐Polyvinyl Alcohol Blends. Issue 12 (15th October 2014) - Nair, Sandeep S.; Sharma, Sudhir; Pu, Yunqiao; Sun, Qining; Pan, Shaobo; Zhu, J. Y; Deng, Yulin; Ragauskas, Art J.
Abstract A new method to prepare nanolignin using a simple high shear homogenizer is presented. The kraft lignin particles with a broad distribution ranging from large micron‐ to nano‐sized particles were completely homogenized to nanolignin particles with sizes less than 100 nm after 4 h of mechanical shearing. The 13C nuclear magnetic resonance (NMR) and 31P NMR analysis showed that there were no major changes in the chemical composition between the starting kraft lignin particles and the nanolignin obtained after 4 h of mechanical treatment. The nanolignin particles did not show any change in molecular weight distribution and polydispersity compared to the original lignin particles. The nanolignin particles when used with polyvinyl alcohol (PVA) increased the thermal stability of nanolignin/PVA blends more effectively compared to the original lignin/PVA blends.